2016
DOI: 10.1144/sp444.4
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic architecture of the Knarr Field, Norwegian North Sea: sedimentology and biostratigraphy of an evolving tide- to wave-dominated shoreline system

Abstract: The Knarr Field is located on the Tampen Spur, Norwegian continental shelf and was discovered in 2008 by the Jordbær well (34/3-1S), with additional resources later added to the field by the Jordbær Vest well (34/3-3S) in 2011. Within the Knarr Field, the Cook Formation is informally divided into the Lower Cook and Upper Cook successions and appears to have prograded from east to west. The Lower Cook consists of Sands 1, 2 and 3 and the Upper Cook consists of Sands 4 and 5, with the sands separated by intrafor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Fungal material was not subdivided (sensu Boulter and Riddick, 1986), and well-preserved wood and parenchyma were also grouped (sensu van der Zwan, 1990 (Gary et al, 2009). This is important for large, gradational palaeoentological datasets, which often include samples that are transitional between hard clusters (Gary et al, 2009;Daly et al, 2011;Erbs-Hansen et al, 2011Churchill et al, 2016;McArthur et al, 2016b). This methodology is particularly appropriate for the Marnoso-Arenacea dataset, which aims to examine the changes in sedimentation from turbidity currents that graded across an area in excess of 3600 km 2 ( Fig.…”
Section: Palynological Processingmentioning
confidence: 99%
“…Fungal material was not subdivided (sensu Boulter and Riddick, 1986), and well-preserved wood and parenchyma were also grouped (sensu van der Zwan, 1990 (Gary et al, 2009). This is important for large, gradational palaeoentological datasets, which often include samples that are transitional between hard clusters (Gary et al, 2009;Daly et al, 2011;Erbs-Hansen et al, 2011Churchill et al, 2016;McArthur et al, 2016b). This methodology is particularly appropriate for the Marnoso-Arenacea dataset, which aims to examine the changes in sedimentation from turbidity currents that graded across an area in excess of 3600 km 2 ( Fig.…”
Section: Palynological Processingmentioning
confidence: 99%
“…The unit has been interpreted as a highly heterogeneous tidal-and wave-influenced succession (Livbjerg and Mjøs, 1989;Steel, 1993 1995; Marjanac and Steel, 1997) organized in a series of regional regressivetransgressive cycles (Marjanac and Steel, 1997). Churchill et al (2017) observed tidal deposits in the lower part and wave deposits in the upper part, while Dreyer and Wiig (1995) and Folkestad et al (2012) recognized wave-deposits in the lower part followed by tidal deposits.…”
Section: Geological Settingmentioning
confidence: 94%
“…2B). Available literature (Dreyer and Wiig, 1995;Folkestad et al, 2012;Churchill et al, 2017) focuses mostly on the Tampen Spur, a different structural element in the Norwegian North Sea ca. 100 km to the NW of the Horda Platform.…”
Section: Geological Settingmentioning
confidence: 99%
“…() on the Cook Formation, Knarr Field, Norway, reported that total sediment chlorite abundance and mean grain coat coverage are greatest in estuarine facies compared to fully marine facies. There is therefore broad concurrence between the modern Ravenglass Estuary and the Jurassic Cook Formation (Churchill et al ., ; Skarpeid et al ., ).…”
Section: Reservoir Quality Implications and Prediction Of Clay‐coat Mmentioning
confidence: 99%